Pengaruh Kualitas Produk Dan Kualitas Terhadap Pelayanan Kepuasan Konsumen (Studi Kasus Pada Restorant Ayam Bakar, Medan) - Riska Febrianti Aulia; Muhammad Irwan Padli Nasution (Jurnal Akuntansi Keuangan dan Bisnis, 2023)
The aim of this research is to find out how the product quality and service of a restaurant affect consumers. This restaurant is quite popular because it has a distinctive taste that is different from other restaurants. The method used in uu research is a qualitative method which uses the results of a questionnaire consisting of 50 people. interviews and documents The location in this study used the purposive area method. The results of the study showed that they were very satisfied with the products of the teticliut restaurant, in terms of sufficient space, strategic so that many of the visitors admired the terachut place both among young people and adults. Apart from a strategic location, the place has facilities such as wifi. private nungan, and karaoke. From the observed results, many visitors are satisfied with the products from the restaurant. From a service perspective, the restaurant is very satisfied.